The Local Dimension of Migration Policymaking - Caponio, Tiziana; Borkert, Maren (IMISCOE Reports, 2010)
This book prompts a fresh look on immigrant integration policy. Revealing just where immigrants and their receiving societies interact everyday, it shows how societal inclusion is administered and produced at a local level. The studies presented focus on three issue areas of migration policy - citizenship, welfare services and religious diversity - and consider cities in very different national contexts. Spanning Switzerland, Italy, Germany, the Netherlands and Canada, the cases display great variety in their theoretical and methodological approaches. In all the countries considered, we see that the local level has an undeniable relevance despite differences in state structures, models of integration and centre-peripheral relations. Particularly for future migration policy research, such a complex comparative exercise thus yields an important universal realisation: the local dimension of migration policymaking matters. This title is available in the OAPEN Library - http://www.oapen.org.